Technical efficiency analysis and profitability of local rice processing in Kwara state, Nigeria - AKANBI, Sheu-Usman Oladipo (2023)
The study seeks to assess the technical efficiency and profitability of local rice processing in Kwara state, Nigeria. The specific objectives are to: (a) estimate the cost and returns of local rice processing; (b) estimate the technical efficiency of the rice processing methods employed; (c) analyze the factors influencing technical efficiency of local rice processing; and (d) identify the constraints to local rice processing in the study area. A two-stage sampling technique was employed to select 120 processors who were randomly selected from a list of registered processors in Edu and Pategi Local Government Areas. The data were analyzed using descriptive statistics, gross margin, Data envelopment analysis and Tobit regression. Majority of the respondents were female (77.5%) and all the processors (100%) use traditional methods for all processing methods except for the milling and destoning stage. The Gross Margin and Capital turnover was estimated to be 142,490 and 1.49 respectively. The processors achieved relatively low overall technical efficiency, pure technical efficiency, and scale efficiency score (0.4965 and 0.820 and 0.5566) respectively. Education level, years of processing experience, use of modern equipment and training on use of processing had positive effects on processing efficiency while labour cost showed negative influence on the rice processing efficiency. This study recommends that more attention should be paid to providing technical training and enhancing accessibility to modern equipment especially to the women processors. Note: $1 = N 430